Tessier No. 3 incomplete cleft: Nasal reconstruction using turbinate mucosal flap - Abbas Asgharali Mistry; Burhanuddin Qayyumi; Taher Abbas Mistry; Chetan Kardile (Wolters Kluwer Medknow Publications, 2016)
Facial clefts are extremely rare congenital deformities, especially Type 3. In 1976, Tessier classified the clefts between 0 and 14 based on the central facial landmarks. The Tessier type 3 facial cleft, also called a nasoocular or a nasomaxillary cleft, results from the disruption of the lateral nasal and maxillary processes. It is characterized by inferior displacement of the medial canthus, superior displacement of the alar base, cleft lip and palate, coloboma of lower eyelids, nasolacrimal abnormalities, cleft of the inferomedial orbital wall, and teleorbitism. Although the literature is replete with classification and morbid anatomy of such cases, surgical management is still a challenge. In this article, we report a Tessier No. 3 incomplete cleft, wherein the turbinate mucosal flap was used for the nasal lining in reconstruction of the nose. Probably, this is the first time that the turbinate mucosal flap is used for reconstruction in Tessier No. 3 cleft.